2015
DOI: 10.1051/bioconf/20150502021
|View full text |Cite
|
Sign up to set email alerts
|

Wine fingerprinting using a bio-geochemical approach

Abstract: Abstract.The wine sector is a billion euro business and therefore subjected to multiple attempts of fraudulent practices. This requires the development of rapid and reliable methods to detect such situations. Several methodologies have been developed based on the chemical profiles of the wines, but they are limited due to the environmental conditions that cannot be controlled. The use of DNA-based detection systems are an emergent research field that have been extended to a wide variety of food products and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
(18 reference statements)
1
4
0
Order By: Relevance
“…Palmela and Óbidos DO, characterised by sandy and clay soils (more recent and with a lower Rb/Sr) respectively, showed lower 87 Sr/ 86 Sr ratios. The observed values are in accordance with reported ratios for a wine from a Portuguese granitic area (0.71203) (Barbaste et al, 2002), and lower than values reported for wines from Douro (0.7130 to 0.7175) (Fernandes et al, 2015), where soils are mainly schistous.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Palmela and Óbidos DO, characterised by sandy and clay soils (more recent and with a lower Rb/Sr) respectively, showed lower 87 Sr/ 86 Sr ratios. The observed values are in accordance with reported ratios for a wine from a Portuguese granitic area (0.71203) (Barbaste et al, 2002), and lower than values reported for wines from Douro (0.7130 to 0.7175) (Fernandes et al, 2015), where soils are mainly schistous.…”
supporting
confidence: 90%
“…These differences could possibly be explained by the inter-year variability, making evident the drawbacks of multi-elemental-based strategies for the determination of geographic origin. Among Portuguese DO, higher concentrations were recently found in wines from the Douro region (Fernandes et al, 2015).…”
mentioning
confidence: 94%
“…Most of the vineyards are installed in soils developed on schists. There is little information on strontium isotopic ratio of soils and wines from Douro [3,5,20]. On the basis of these considerations, a study was developed to examine the variation of 87 Sr/ 86 Sr in wines from Douro region taking into account the effect of vineyard location and grapevine variety.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, instead of aiming to define a unique technology, the integration of two-dimensional strategies, one for geographical origin determination and another for varietal identification and quantification, can be a more convenient and reliable way of tackling this issue. This type of approach has been already suggested by Fernandes et al [31] as a bio-geochemical strategy, considering the grapevine composition through a biological method, and the definition of provenance based on geochemical determination.…”
Section: The Importance Of An Integrated Strategymentioning
confidence: 99%
“…Some of the most widely applied methods to assess the botanical and geographical origin of wine are spectroscopic and/or spectrometric, such as ultra-performance liquid chromatography (UPLC), Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS), nuclear magnetic resonance (NMR), ultraviolet-visible spectrophotometry (UV-vis), near-infrared (NIR), mid-infrared (MIR), high-performance liquid chromatography (HPLC), gas chromatography mass spectrometry (GC-MS), inductively coupled plasma optical emission spectrometry (ICP-OES), and inductively coupled plasma mass spectrometry (ICP-MS), among others. All these are high-throughput approaches requiring the use of somewhat complex statistical analyses and, most of the time, a big data set from the defined region considering several production years and varieties to develop a reliable database [31].…”
Section: Determination Of the Region Of Proveniencementioning
confidence: 99%